Proteolysis in Mozzarella Cheeses Manufactured by Different Industrial Processes - Costabel , Luciana María (2007)
The objective of the present study was to investigate the influence of stretching temperature, fat content,and time of brining on proteolysis during ripening of Mozzarella cheeses. Seventeen cheese-making experiments (batches) were carried out on an industrial scaleon successive days, following the standard procedure with some modifications. Fat content of cheese milk, temperature at the stretching step, and time of brinining varied from one batch to another as required by the experimental design, outlined by a surface response model. Proteolysis was assessed during ripening of samples, which was prolonged for at least 3 months, by means of electrophoresis, nitrogen fractions, and soluble peptide mapping. The amount of soluble nitrogen at pH 4.6 was not significantly different in cheeses obtained by diverse procedures, but it increased during ripening of all samples. This result was coincident with the breakdown of ás1- and â-caseins evidenced by electrophoresis, which reached similar extents at late stages of ripening, regardless of the cheese-making process. Multivariate analysis on soluble peptide profiles obtained by liquid chromatography also detected sample grouping according to ripening time, but did not evidence any separation caused by the cheese-making technology.Weconcluded that the changes in the cheese-making process assayed in this work were insufficient to produce significant differences in proteolysis of the cheeses. Ripening time had more influence on proteolysis of Mozzarella cheeses than any other assayed variable.ás1- and â-caseins evidenced by electrophoresis, which reached similar extents at late stages of ripening, regardless of the cheese-making process. Multivariate analysis on soluble peptide profiles obtained by liquid chromatography also detected sample grouping according to ripening time, but did not evidence any separation caused by the cheese-making technology.Weconcluded that the changes in the cheese-making process assayed in this work were insufficient to produce significant differences in proteolysis of the cheeses. Ripening time had more influence on proteolysis of Mozzarella cheeses than any other assayed variable.